Pemberdayaan Masyarakat di Wilayah Benda Baru Melalui Pelatihan Instalasi Listrik Rumah Tangga - Kartika Sekarsari; Heri Kusnadi; Sunardi; Oky Supriadi (Universitas Lancang Kuning, 2020)
The Community empowerment through an activity related to the provision of specific skills can support its independence. Technical training of simple home electrical installation is one form of Community Service (PKM) which contributes to supporting independence in the community, especially residents who live on Jln. H. Nurleman Benda Baru Pamulang, South Tangerang City. Training in the form of community independence for simple home electrical installations is taught through learning material related to electricity, K3, and the implementation of electrical installation practice using training modules that have been prepared. There is a curiosity about knowledge related to electricity, good understanding of knowledge, agility and skill in mastering the practice of electrical installations according to procedures, and having a cautious attitude in the installation of electrical installations will be the main capital for a person to be an entrepreneur. This can also be a solution for the lack of orderly installation of electricity in residential homes